PRACTICE TRAINING OF ENERGY MANAGERS – A NEW CLASS OF ENGINEERING AND ECONOMICS PROFESSIONALS - Roman S. Golov; Vyacheslav Yu. Teplyshev; Aleksey V. Myl’nik (Высшее образование в России)
Abstract. The article analyzes the activity of Russia’s first chair of «Energy service and energy saving management» established at the Institute of Management, Economics and Social Technologies of Moscow Aviation Institute (National Research University). The focus of the department staff is training of specialists in energy management for various industries. The first part of the article is devoted to analysis of the results achieved by the department. The main part of the study contains a detailed description of the structure and developed by the authors in collaboration with major European energyNefficient companies, engineering and economic education model called “an arrow of energy efficient competencies”. The authors dwell on the content of its individual units and components of their areas of study.